Nervous nineties: uncertainties cloud decade for the Third World (North-South Institute OttawaCA, 1990)
Analyzes the impact of the Canadian government's ODA cuts in 1989, and the likely sequel in 1990. Looks at the debt situation, world trade and structural adjustment. Examines women's progress in the last decade and the Guyana Support Group. Focuses on the implications of Canada's taking its full place in the Organization of American States and the changing face of Southern Africa.
DC